2021
DOI: 10.1098/rspb.2020.3118
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational plasticity and the capacity to adapt to low salinity in the eastern oyster, Crassostrea virginica

Abstract: Salinity conditions in oyster breeding grounds in the Gulf of Mexico are expected to drastically change due to increased precipitation from climate change and anthropogenic changes to local hydrology. We determined the capacity of the eastern oyster, Crassostrea virginica , to adapt via standing genetic variation or acclimate through transgenerational plasticity (TGP). We outplanted oysters to either a low- or medium-salinity site in Louisiana for 2 years. We then crossed adult parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Low salinity conditions resulted in slower growth and reduced body size at metamorphosis, which was associated with mortality at later stages [26]. While they did not find evidence of strong transgenerational plasticity, they did find high heritability for body size under low salinity conditions, suggesting that there is ample genetic variation for this trait to evolve in response to declining salinity in the future [26].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Low salinity conditions resulted in slower growth and reduced body size at metamorphosis, which was associated with mortality at later stages [26]. While they did not find evidence of strong transgenerational plasticity, they did find high heritability for body size under low salinity conditions, suggesting that there is ample genetic variation for this trait to evolve in response to declining salinity in the future [26].…”
mentioning
confidence: 89%
“…Griffiths et al teased apart the roles of standing genetic variation and transgenerational plasticity in low salinity tolerance of the Eastern oysters in the Gulf of Mexico, which is predicted to experience declining salinities under climate change. Low salinity conditions resulted in slower growth and reduced body size at metamorphosis, which was associated with mortality at later stages [26]. While they did not find evidence of strong transgenerational plasticity, they did find high heritability for body size under low salinity conditions, suggesting that there is ample genetic variation for this trait to evolve in response to declining salinity in the future [26].…”
mentioning
confidence: 89%
“…The role of methylation in environmental responses of oysters is of particular interest because this species faces a rapidly changing environment, and epigenetic methylation is a possible mechanism for transgenerational inheritance of environmentally responsive phenotypes. Our previous work with C. virginica provides evidence both for environmentally induced methylation differences and for transgenerational inheritance in oysters, with parental acclimation to sites with differing salinity conditions contributing to variation in larval traits (Griffiths et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work with C . virginica provides evidence both for environmentally induced methylation differences (Johnson & Kelly, 2020) and for transgenerational inheritance in oysters, with parental acclimation to sites with differing salinity conditions contributing to variation in larval traits (Griffiths et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that epigenetic divergence exceeds genetic divergence in some Louisiana oyster populations ( Johnson and Kelly, 2020 ). However, another study found no evidence for parental carryover effects on larval tolerance of low-salinity conditions, even after parental stocks were maintained at low-salinity conditions for 2 years ( Griffiths et al, 2021 ). While our studies were limited to characterizing the performance of the progeny of wild oysters (i.e.…”
Section: Discussionmentioning
confidence: 99%